Analgesic and antipyretic activity of methanolic extract of Leucas Clarki in animal models - Swain, Truptirekha; Pradhan, Rashmita; Barik, Debasish (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Search for an indigenous safe and effective analgesic and antipyretic agent continues to be an exciting area of research. The objective of this study was to evaluate the analgesic and antipyretic activity of methanolic extract of Leucas clarki, in animal models. Methods: Analgesic activity was evaluated in albino mice by acetic acid induced writhing test. Antipyretic study was carried out in albino rats by inducing pyrexia with brewer’s yeast. Analgesic activity was expressed as percentage of reduction in number of writhings compared to vehicle (Tween-80) and antipyretic activity was expressed as reduction of rectal temperature compared to basal temperature, after 18 hours of induction of pyrexia. Leucas clarki extract was administered at 3 doses (100,200,400mg/Kg) intraperitoneally. Student’s paired and unpaired “t” test was applied to test significance. Results: Methanolic extract of Leucas clarki (MLC) at dose 200 mg and 400mg /kg produced 19.17% & 32.03% of reduction of no. of writhing induced by acetic acid compared to that of Tween 80 treated control mice, However this is less compared to aspirin treated control rats. In model of pyrexia all the three doses of MLC produced significant reduction of rectal temperature compared to basal temperature (18hrs). Antipyretic effect was appreciated at very first hour and persisted till the end of 6 hours like that of paracetamol. Both 100 &200 mg/kg MLC were equivalent in potency as that Paracetamol (33mg/kg I.P) and 400mg/kg was even better than Paracetamol. Conclusions: Methanolic extract of Leucas clarki possesses excellent antipyretic and analgesic property.